Biomimetic Scaffolds of Calcium-Based Materials for Bone Regeneration - Ki Ha Min; Dong Hyun Kim; Koung Hee Kim; Joo-Hyung Seo; Seung Pil Pack (Biomimetics)
Calcium-based materials, such as calcium carbonate, calcium phosphate, and calcium silicate, have attracted significant attention in biomedical research, owing to their unique physicochemical properties and versatile applications. The distinctive characteristics of these materials, including their inherent biocompatibility and tunable structures, hold significant promise for applications in bone regeneration and tissue engineering. This review explores the biomedical applications of calcium-containing materials, particularly for bone regeneration. Their remarkable biocompatibility, tunable nanostructures, and multifaceted functionalities make them pivotal for advancing regenerative medicine, drug delivery system, and biomimetic scaffold applications. The evolving landscape of biomedical research continues to uncover new possibilities, positioning calcium-based materials as key contributors to the next generation of innovative biomaterial scaffolds.